ANALYSIS OF ECOWAS QUEST FOR REGIME SURVIVAL VERSUS REPUBLIC OF NIGER: ECONOMIC AND POLITICAL IMPLICATIONS - Ukpere, Wilfred; Frank, Etim Okon (Annals of Spiru Haret University. Economic Series, 2024)
The study explores ECOWAS quest for regime survival in the aftermath of the collapse of the democratic government in the Republic of Niger, being the fifth country in the row in West Africa within three (3) years. It sought to unveil the latent reasons behind ECOWAS stand, interrogate whether it was acting as a proxy and identify the linkages between the destruction of Nord-Stream Gas Pipeline phase 1 and 2, the renewed interest in Trans-Sahara Gas Pipeline (TSGP) and ECOWAS pursuit of regime survival. The analysis approached the study through an exploratory and diagnostic method, which explored historical and time-series events in the analysis. The procedure revealed that wherever democratic regimes failed to add value to the lives of citizens through democratic accountability, the people will embark on protest actions out of relative deprivation that confront them. Military coup d’etat is an extreme form of protest at the level of supplantment as witnessed in Niger. It further disclosed that ECOWAS quest for regime survival is unconnected with TSGP project meant to convey gas from Nigeria through Niger Republic via Algeria to western Europe through Italy. The declaration by the coupists that Niger will not honour its own part of the contract any longer would result in extreme dependence of Western Europe on Russia for gas. The logical alternative is to get ECOWAS to embark on regime restoration in order to honour the pipeline contract and possibly free Europe from the stranglehold of Russia. The analysis concluded that Russian -Ukraine kind of war looms in Niger, which is capable of engulfing Nigeria and the sub-region.